Law, nation and (imagined) international communities - R. Buchanan; S. Pahuja (Law Text Culture, 2004)
Although it was published more than 20 years ago, in a world that was geopolitically dramatically different from our own, it is difficult to approach the subject of nation without invoking Benedict Anderson’s Imagined Communities. This small book has come to serve as an almost mandatory point of reference for academic discussions of the modern nation. And although many disagree with Anderson’s analysis that ‘from the start, nation was conceived in language not in blood’ (Anderson 1991: 133), in the wake of his book it is difficult to consider nation and its relation to community without also considering the modern discursive and cultural forms through which they are each conjured and connected. That is, Anderson saliently observed that the link between community and nation is made, not found.